The Oncology Safety of Diagnostic Hysteroscopy in Early-Stage Endometrial Cancer: A Systematic Review and Meta-Analysis - Du, Yi; Xu, Yu; Qin, Zhaojuan; Sun, Liang; Chen, Yali; Han, Ling; Zheng, Ai (Frontiers in Oncology, 2021)
Background: Hysteroscopy is becoming a common method for the diagnosis of uterine disorders in developed countries. However, hysteroscopy might worsen the prognosis of endometrial cancer because it could cause cancer dissemination into the peritoneal cavity through the fallopian tubes. Objective: The aim of this systematic review and meta-analysis was to explore the oncological safety of hysteroscopy for early-stage endometrial cancer. Search strategy: Eligible studies were obtained from PubMed, Embase, and the Cochrane Library up to September 22, 2020. Selection criteria: Studies which compared the oncological safety of hysteroscopy with other methods were included. Data collection and analysis: A total of 3980 patients were included in this study, of whom1357 patients had undergone hysteroscopy and2623 had not. Main results: There was no significant association between hysteroscopy and worse prognosis in early-stage endometrial cancer (disease-free survival: log risk ratio[logRR] -0.22; 95% confidence interval [CI], -0.54 to 0.1; p=0.97; overall survival: logRR 0.03; 95% CI, -0.05 to 0.11; p=0.02; disease-specific survival: logRR 0.03; 95% CI, -0.03 to 0.10; p=0.00). Conclusion: This study suggests that hysteroscopy is a safe diagnostic and treatment method, and has no significant effect on the prognosis of early-stage endometrial cancer.